Evaluasi Program Kampung Keluarga Berencana di Kota Tanjungpinang (Studi Kasus Kampung Bulang Kecamatan Tanjungpinang Timur) - Rahmi Widia Purnama; Fitri Kurnianingsih; Rudi Subiyakto (Lembaga Pengembangan Kinerja Dosen, 2023)
One of the recognized stages in addressing population growth is the Family Planning Program. In essence, the results of the Family Planning Program are beneficial for the growth and development of Indonesian society. Community participation is very influential in the family planning program, especially in improving the quality of life of the community at the village level or equivalent to the family planning program and other development programs that have been adjusted by each region. The evaluation of the family planning program in Kampung Bulang sub-district aims to obtain comprehensive information on the implementation and implementation of family planning programs in increasing family resilience and welfare. In this study, researchers used descriptive research using a qualitative approach, with primary and secondary data sources. This study uses the Program Evaluation Theory according to Wirawan, where in this theory there are five indicators consisting of (1) Input Evaluation, which aims to assess the adequacy of the Quantity and Quality of the Family Planning Program. (2) Process Evaluation, which aims to see or monitor how far the activities have been carried out. (3) Output Evaluation, which aims to see whether the Family Planning Program is running well or vice versa. (4) Outcome Evaluation which aims to see the results of whether the community understands the importance of the Family Planning Program. (5) Impact Evaluation, which aims to assess changes that occur in society. The conclusion of the program researchers is that it is running well, but it must continue to raise public awareness for the family planning program. The government also needs to reaffirm family planning not only in certain circumstances but for national needs.